Exploring the Relation Between Maternal Vitamin Intake and Child Development - Mawia Al-Beshti; Omaima Al-Hindawi; Mervat Adel; Heeba Al-Mabrouk (AlQalam Journal of Medical and Applied Sciences, 2025)
Good nutrition during pregnancy is very important for the baby’s growth and health before and after birth. This study examined how taking vitamins during pregnancy affects the child’s development. We asked 40 mothers about their vitamin intake, health during pregnancy, and their children’s growth. We found that 90% of the mothers took vitamins, and most of them started in the first three months of pregnancy. Almost all the children (98%) were born with a normal weight, and 95% showed normal development in movement and language in their first two years. However, 40% of the mothers had anemia, which shows that more attention is needed for iron intake during pregnancy. We also found that mothers who started taking vitamins later in pregnancy (after the first three months) or had anemia were more likely to have children with anemia or weaker immunity in early childhood. These results highlight the importance of educating mothers about nutrition during pregnancy and improving healthcare services to ensure mothers and children stay healthy.